Cardioprotection by remote ischemic conditioning is transferable by plasma and mediated by exosomes. (25th November 2020) - Lassen, T.R; Just, J; Hjortbak, M.V; Jespersen, N.R; Stenz, K.T; Gu, T; Yan, Y; Su, J; Nyengaard, J.R; Kristiansen, S.B; Drasbek, K.R; Kjems, J; et al.
Abstract: Background: Remote ischemic conditioning (RIC) by brief periods of limb ischemia and reperfusion protects against ischemia-reperfusion injury. However, the mechanism is unknown. Purpose: We studied the role of exosomes for mediating the cardioprotective signal and whether they accumulate in injured myocardium. Methods: Blood samples from 12 healthy male volunteers were obtained prior to and one hour after RIC. Plasma obtained before and after RIC (n=4) (P-Pre and P-Post) was used to evaluate the transferability of RIC. Pre- and Post-RIC plasma (n=8) was separated into an exosome rich fraction (Exo-Pre and Exo-Post) and an exosome depleted fraction (Prot-Pre and Prot-Post) by size exclusion chromatography. All studies were carried out in duplicate samples from each volunteer. Infarct size was compared in Sprague-Dawley rat hearts perfused with plasma, exosomes and exosome depleted fractions in a Langendorff model. We investigated changes in the miRNA content of the exosomes after RIC by a human miRNA panel. Additionally, fluorescently labeled exosomes isolated from C2C12 cells were used to assess accumulation in injured myocardium in an in vivo rat model. Rats were divided into an infarct group (n=6) (left anterior descending artery ligation) and a sham group (n=6) (without ligation). Labelled exosomes were injected in the femoral vein prior to reperfusion. Exosome-accumulation in infarcted or sham myocardium was evaluated. Results: P-Post reduced infarct size by 15% points compared with P-Pre (55±4% vs 70±6%, p=0.03) (Fig. 1a). Exo-Post reduced infarct size by 16% points compared with Exo-Pre (53±15% vs 68±12%, p=0.03) (Fig. 1b). Prot-Post did not affect infarct size compared to Prot-Pre (64±3% and 68±10%, p>0.99). We found miRNA-16, miRNA-144 and miRNA-451 to be upregulated in exosomes after RIC and the mTOR-pathway as a potential target for these miRNAs. In the in vivo model, labelled exosomes accumulated more intensively in the infarct area than in remote areas and sham hearts (Fig. 1c). Conclusion: Cardioprotection by RIC is mediated by exosomes with a changed miRNA profile and exosomes accumulate in injured myocardium. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Novo synergy